Rekomendasi Apoteker Komunitas Saat Menghadapi Permintaan Swamedikasi Diare yang Disertai Alarm Symptoms - Setiadi, Adji Prayitno; Istiqomah, Reza Amelia; Octafelia, Yustina; Wibowo, Yosi Irawati; Brata, Cecilia; Setiawan, Eko; Halim, Steven Victoria (Poltekkes Kemenkes Tanjung Karang, 2022)
Appropriate recommendations given by pharmacists play a critical role in determining the efficacy and safety of self-medication practices in pharmacies, including in the case of diarrhea with alarm symptoms. This observational study with a cross-sectional design aims to determine the profile and appropriateness of recommendations given by pharmacists in Surabaya when they faced self-medication requests for diarrhea with alarm symptoms. Data were collected using a questionnaire consisting of two parts, i.e., participants’ characteristics and one case of adult diarrhea with alarm symptoms. The case used was newly developed and the content had been validated. The content validation and the determination of appropriate recommendations given by pharmacists involved experts in clinical pharmacy, community pharmacy, and public health. The final data were analyzed and presented descriptively. A total of 160 pharmacists were involved in this study, the majority of whom were managing pharmacists (82.50%), female (85.50%), and have been working as pharmacists for 1 to 7 years (48.75%). Most pharmacists (56.87%) gave more than one type of recommendation, the majority of whom recommended dispensing of pharmaceutical products accompanied by a referral to physicians (21.88%). Only 42 pharmacists (26.25%) gave appropriate recommendations including referral to physicians (18.13%) or referral accompanied by pharmaceutical product (6.88%) and non-pharmacology recommendations (1.25%). Need assessment is required to identify interventions preferred by pharmacists to optimize their role in promoting responsible self-medication practices.